Cerebral Oxygenation During Neonatal Intubation–Ancillary Study of the Prettineo–Study - Vedrenne-Cloquet, Meryl; Breinig, Sophie; Dechartres, Agnes; Jung, Camille; Renolleau, Sylvain; Marchand-Martin, Laetitia; Durrmeyer, Xavier (Frontiers in Pediatrics, 2019)
Purpose: This study aimed to describe cerebral Near InfraRed Spectroscopy (NIRS) profiles during neonatal intubation using two different premedication regimens. Methods: Neonates requiring non-emergency intubation were enrolled in an ancillary study, conducted in two French Neonatal Intensive Care Units participating in a larger on-going multicenter, double blind, randomized, controlled trial. Patients were randomly assigned to the “atropine-propofol” (Prop) group or the “atropine-atracurium-sufentanil” (SufTrac) group. Regional cerebral oxygen saturation (rScO2), pulse oxymetry (SpO2), mean arterial blood pressure (MABP), and transcutaneous partial pressure of carbon dioxide (TcPCO2) were collected at 9 predefined time points from 1 min before to 60 min after the first drug injection. The two primary outcomes were a decrease in rScO2 value >20% from baseline and a decrease in fractional cerebral tissue oxygen extraction (FTOE) value >10% from baseline, at any time point. Secondary outcomes included physiological parameters changes over time and correlations between mean arterial blood pressure, and FTOE at different time points. Descriptive results were obtained and exploratory statistical analyses were performed for 24 included patients. Results: rScO2 decreased in 5/11 (46%) infants from the Prop group and 10/13 (77%) from the SufTrac group (p = 0.11); FTOE decreased in 10/11 (91%) infants from the Prop group, and 12/13 (92%) from the SufTrac group (p = 0.90). rScO2 values decreased over time in both groups, whereas FTOE's pattern appeared more stable. SpO2 and transcutaneous TcPCO2 seemed more preserved in the Prop group while MABP seemed more preserved in the SufTrac group. No important correlation was observed between MABP and FTOE (r = 0.08 to 0.12 across the time points). Conclusion: Our results suggest a frequent decrease in cerebral oxygenation without obvious impairment in cerebral autoregulation during neonatal intubation with premedication. This study confirms the feasibility and the informative value of cerebral NIRS monitoring in this setting. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT02700893.